2013
DOI: 10.1103/physrevc.87.044329
|View full text |Cite
|
Sign up to set email alerts
|

Spin instabilities of infinite nuclear matter and effective tensor interactions

Abstract: We study the effects of the tensor force, present in modern effective nucleon-nucleon interactions, in the spin instability of nuclear and neutron matter. Stability conditions of the system against certain very low energy excitation modes are expressed in terms of Landau parameters. It is shown that in the spin case, the stability conditions are equivalent to the condition derived from the spin susceptibility, which is obtained as the zero-frequency and long-wavelength limit of the spin response function calcu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 45 publications
2
36
0
Order By: Relevance
“…Another interesting point of Ref. [13] is that the authors have shown that instabilities manifest themselves in another quantity that is easier to calculate than the full response function, namely the spin susceptibility that is obtained as a proper limit to zero energy and momentum transfer of Eq. (75).…”
Section: Instabilitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Another interesting point of Ref. [13] is that the authors have shown that instabilities manifest themselves in another quantity that is easier to calculate than the full response function, namely the spin susceptibility that is obtained as a proper limit to zero energy and momentum transfer of Eq. (75).…”
Section: Instabilitiesmentioning
confidence: 99%
“…[13] an interesting comparison between instabilities induced by zero-range and finite-range interactions is carried out. It has been shown that in the case of zero-range interactions the addition of tensor terms favours the appearance of instablities but this is not the case for the finiterange forces.…”
Section: Instabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It consists in describing the ph interaction in terms of Landau parameters, including both central and tensor components, and calculating the RPA response function with no further approximations. Actually we shall apply and extend the method previously developed to obtain the RPA response function [7,9,10,11]. We shall explore the convergence of the response in terms of the number of Landau parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The parameters are usually fixed to reproduce some selected spinorbit splittings, with either a partial or a complete fit of parameters. However, the parametrizations can lead to the appearance of unphysical instabilities of the Fermi surface both in the zero-and long-range regimes [16][17][18]. To avoid them we have proposed [19,20] to incorporate into the fitting procedure the constraints obtained from linear response theory.…”
mentioning
confidence: 99%